Intraoral dermoid cyst: report of two cases - Priya, Ratna; Virmani, Nitish; Dabholkar, Jyoti (International Surgery Journal, 2016)
Dermoid cysts are benign cystic abnormalities lined by squamous epithelium. They account for 1.6% to 6.9% of all cysts in the head and neck region. They constitute less than 0.01% of all oral cavity cysts. Here we present two case reports of dermoid cyst in the floor of mouth. In both the cases patients presented with floor of mouth asymptomatic swelling since many years. Intraoral surgical excision of the lesion was carried out under general anesthesia. . Transverse incision was taken in the floor of the mouth, extending between both the premolars on either side, over the most prominent part of the swelling. Wharton’s duct was identified before incising. Once capsule was reached, blunt dissection was done to free the capsule. Histopathology in both the cases was suggestive of a dermoid cyst. An intraoral approach is preferred in cases of cysts above the mylohyoid muscle. Intraoral approach gives a better cosmetic and functional result. Dermoid cyst, though rare should be kept in mind as a differential in floor of mouth lesions.